2018
DOI: 10.1038/s41598-018-21590-9
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Seasonal Contribution of Observed Biogenic Sulfate Particles to Cloud Condensation Nuclei

Abstract: Biogenic sources contribute to cloud condensation nuclei (CCN) in the clean marine atmosphere, but few measurements exist to constrain climate model simulations of their importance. The chemical composition of individual atmospheric aerosol particles showed two types of sulfate-containing particles in clean marine air masses in addition to mass-based Estimated Salt particles. Both types of sulfate particles lack combustion tracers and correlate, for some conditions, to atmospheric or seawater dimethyl sulfide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
149
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(166 citation statements)
references
References 126 publications
(94 reference statements)
17
149
0
Order By: Relevance
“…Our analysis of NAAMES‐1 and NAAMES‐2 cloud properties in combination with the analysis of aerosols by Sanchez et al () suggests that cloud microphysical properties over the North Atlantic Ocean are being influenced by the phytoplankton bloom, leading to a cloud brightening effect. However, meteorological differences between the campaigns also play an important role, and therefore, the magnitude of the cloud property changes due to biogenic activity remains uncertain.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Our analysis of NAAMES‐1 and NAAMES‐2 cloud properties in combination with the analysis of aerosols by Sanchez et al () suggests that cloud microphysical properties over the North Atlantic Ocean are being influenced by the phytoplankton bloom, leading to a cloud brightening effect. However, meteorological differences between the campaigns also play an important role, and therefore, the magnitude of the cloud property changes due to biogenic activity remains uncertain.…”
Section: Resultssupporting
confidence: 89%
“…A large increase in aerosol mass and CCN concentrations is observed between the NAAMES-1 and NAAMES-2 campaigns. Sanchez et al (2018) used a combination of radon concentrations, combustion tracers, and back trajectories to determine that few aerosols originated from continents during NAAMES-1 and NAAMES-2 with most aerosols having biogenic marine sources. These findings also agree with previous work that found that variances in marine CCN concentrations can be largely explained by DMS from a phytoplankton bloom over the North Atlantic Ocean (Cavalli et al, 2004;Yoon et al, 2007) and in other oceanic basins (Andreae et al, 1995;Charlson et al, 1987;Hegg et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They attributed this to the important influence of entrainment of particles from the free troposphere to the MBL. Sanchez et al () further explored the seasonal aerosol variability during NAAMES and concluded that changes in the ocean ecosystem and resulting DMS emissions give rise to an increased aerosol SO 4 2‐ contribution to CCN observed during springtime bloom periods, both from new particle formation and from condensation onto existing particles. The NAAMES aerosol‐cloud sampling strategy followed a similar set of stacked aircraft legs used by others in ACI‐focused campaigns (Crosbie et al, ; Sorooshian et al, ) and sampled clouds under both typical marine aerosol loadings (order of hundreds per cm 3 of air) and severely aerosol‐depleted conditions (order of tens per cm 3 of air).…”
Section: History Of Wnao Researchmentioning
confidence: 99%
“…Nevertheless, atmospheric studies powered by new analytical techniques (Kulmala et al, 2014) and modeling have shown instances where marine DMS controls ultrafine aerosol particle formation in the Arctic (Leaitch et al, 2013;Park et al, 2017), temperate North Atlantic (Sanchez et al, 2018), Antarctica (Yu and Luo, 2010) and the tropical South Pacific atmospheres (Modini et al, 2009). Moreover, Quinn et al (2017) recently reported that DMS-derived aerosols dominate cloud condensation nuclei populations over most of the global ocean.…”
Section: Introductionmentioning
confidence: 99%